Infantile systemic hyalinosis in siblings: clinical report, biochemical and ultrastructural findings, and review of the literature. - Stucki, U; Spycher, M; Eich, G; Rossi, A; Sacher, P; Steinmann, B; Superti-Furga, A (2001)
A boy presented at age 3.5 months with joint contractures, restlessness, and pain on handling. His skin was thickened and there were livid-red macular lesions over bony prominences. Infantile systemic hyalinosis (ISH) was diagnosed, a presumably autosomal recessive, progressive, and painful disorder of as yet unknown pathogenesis. Observation over three years confirmed the diagnosis as typical changes, such as nodules on both ears, pearly papules in the perinasal folds and on the neck, fleshy nodules in the perianal region, and gingival hypertrophy, developed. Skin lesions and painful joint contractures progressed in spite of intense physiotherapy, and at age 3, the child had marked motor disability. The central nervous system (CNS) appeared to be intact and the infant showed normal mental development. Radiologic findings included marked generalized osteopenia, osteolytic erosions in the metaphyses of the long bones, and cortical thinning. Electron microscopy of two skin biopsies demonstrated deposition of floccular amorphous substance that was abundant around, and appeared to originate from, small blood vessels in the dermis, partially interfering with collagen fiber formation. Lysosomal inclusions were not seen. Serum acid hyaluronidase activity was within the normal range, and the synthesis of hyaluronic acid and proteoglycans in cultured skin fibroblasts was similar to that of control cells. A younger sister presented at age two months with painful joint contractures and discrete livid-red macules over both malleoli, and showed a similar progression of the disorder over the first year of life. The diagnosis of ISH should be considered in infants and children presenting with painful joint contractures and skin lesions. The pathogenesis of this disabling and disfiguring disorder remains unclear. Our data confirm probable autosomal recessive inheritance, and do not support lysosomal storage, hyaluronidase deficiency, or a primary collagen disorder, but indicate that the amorphous material accumulating in the skin and articular soft tissues may originate from the blood circulation.